Home market effects and the single-sector Melitz model - Gabriel J. Felbermayr; Benjamin Jung (Center for Economic Studies and ifo Institute (CESifo), 2011)
Increasing-returns-to-scale imperfect competition trade models predict a more than proportionate relationship between the larger country's share in world endowments and its share in producing firms: the so called home market effect (HME). While this result plays a key role in empirical testing, its theoretical foundation typically posits a linear, friction-free and perfectly competitive outside sector. Replacing this assumption with firm heterogeneity and Melitz (2003) type selection-into-exporting, we demonstrate the existence of a weak and a strong HME. The HMEs are generally non-linear; they are magnified by lower trade costs or more pronounced productivity dispersion. The weak version of the HME continues to hold for general sampling distributions and if the conventional sorting condition fails. In terms of demand shares, a HME holds if demand shocks are due to endowment shocks but reverses in the case of productivity shocks. Finally and in contrast to the model with an outside sector, trade liberalization leads to convergence of real per capita income.
Keywords: F12; R12; 330; home market effect; monopolistic competition; heterogeneous firms; economic geography; Außenwirtschaft; Außenhandelsliberalisierung; Wirtschaftsstruktur; Außenhandelsstruktur; Monopolistischer Wettbewerb; Wirtschaftsgeographie; Theorie